(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2022)
To date, Malaysian law does not provide for any offence for those who carry out corporal punishment either at school or at home, unless the punishment carried out leads to physical and mental injury. This is because corporal punishment is considered a tradition and practice that is still widely accepted in our society today. In Malaysia, whipping and some other corporal punishments are still practiced in schools with guidelines and procedures set by the Ministry of Education Malaysia, for example through the Education (School Discipline) Regulations 1959 and Professional Circular (SPI) No. 8/1983. However, the justification behind the implementation of corporal punishment is often disputed and its implementation is often considered unnecessary, as it can have a negative impact on children. Therefore, this article is an important to study concerning the need and rationale behind the implementation of corporal punishment both at home and in school. This qualitative study uses ethnographic methods through analysis via various theories, and the thought of several schools of jurisprudence, such as sociological, naturalist and utilitarianist thought, to tackle the issue of execution of corporal punishment on children. The study finds that corporal punishment is essentially not accepted by the majority of jurisprudents if it leads to injury and harm in children. However, there are exceptions for problematic students and children to be punished for the purpose of educating them, subject to certain guidelines so as not to cause injury to the recipient of the punishment. The implementation of corporal punishment has, in fact, its own advantages and disadvantages, depending on the way the children accept the punishment. However, from the perspective of social education, it is found to have a more positive impact in building moral principles and ethics in children. Keywords: Corporal punishment, children, physical injury, sociology, naturalism, utitarianism Full text: PDF